Increasing the Millennial Generation's National Defense Awareness through Citizenship Education Learning - Dadang Mulyana (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2024)
This research aims to investigate the effectiveness of learning methods in increasing the awareness of defending the country of the millennial generation through a Citizenship Education approach. This approach is considered important considering the important role of national defense in building awareness of social responsibility and concern for the country. This research uses a qualitative approach with descriptive methods. The research results show that through citizenship education that is integrated and oriented towards the needs of the millennial generation, they can increase their awareness of defending their country. By providing an understanding of national values, teaching critical thinking skills, encouraging open dialogue, and providing direct experience through field projects, the millennial generation can become active and responsible citizens in developing the country. This has a positive impact in strengthening the foundations of democracy, increasing participation in the country's development, and advancing the overall well-being of society.